The future of branding - Srivastava, Rajendra K.; Thomas, Gregory Metz (New Delhi, India ; Thousand Oaks, California : SAGE Publications, 2016)
"New ideas change the world. From social movements to scientific discovery the power of an idea is to reshape the world, who we are, and how we live. Changes in the increasingly dynamic competitive environment require a focus on what should be done, not just what is currently done. The inspiration for this book is to provide an outlet for cogent ideas that will help managers build and maintain brands in the future marketplace. Written by the leading minds management from around the globe who are redefining best practices in managing brands, It examines the future of branding on key concepts including brand performance management, brand strategy, brand building, revitalizing brands, brand valuation, brand analysis, brand protection, and brand experience"--Provided by publisher.
Section I. Brand strategy. Selecting the brand architecture to match your strategy / Jean-Noël Kapferer -- A strategic approach to grow profits : defining, measuring, and maximizing customer value / V. Kumar and Bharath Rajan -- Branding in retail / Lluis Martinez-Ribes -- Section II. Brand building. Brand identity : brand naming process and brand linguistics in the international context / Bernd Schmitt and Shi Zhang -- The six-station model of corporate identity : developing and assessing the model / Jean Yannis Suvatjis and Leslie de Chernatony -- Brand development processes and planning / Kevin Lane Keller -- Managing the brand experience / Bernd Schmitt -- Rethinking brand development in an interactive marketplace / Don E. Schultz -- Luxury brands / Vanessa M. Patrick and Henrik Hagtvedt -- The dynamics of brand trust / Gregory M. Thomas -- Section III. Leveraging brands. Branding and emerging markets / Martin Roll -- Opportunities and risks in co-branding and licensing / Jeffrey Parkhurst -- Brand revitalization / Kevin Lane Keller -- Brand identity strategy for mergers and acquisitions / Srinivas Reddy and Anupam Jaju -- Section IV. Brand performance management. The great debate : managing brands versus managing customers / Werner Reinartz -- Brand imperative : protecting your most valuable assets / Jeffery Andrien, Paul Benoit, and Philip C. Zerrillo -- Hidden value of brands : brands in mergers and acquisitions / S. Cem Bahadir -- Role of brands in managing innovation / Rajendra Srivastava.
Includes bibliographic references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Branding (Marketing); Strategic planning; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Branding (Marketing); Strategic planning; elektronické knihy; electronic books